INCREASING LEARNING OUTCOMES OF CHRISTIAN RELIGIOUS EDUCATION AND CHARACTERISTICS OF GIVING WITH A HAPPY HEART THROUGH THE READING GUIDE LEARNING METHOD FORSTATE VI STATE SCHOOL STUDENTS 064982 MEDAN, ACADEMIC YEAR 2021/2022 - Bertawati Bangun (Sean Institute, 2022)
Improving Learning Outcomes of Christian Religious Education and Character Basic Materials Giving with a Happy Heart Through the Reading Guide Learning Method for Class VI Students of SD Negeri 064982 Medan Academic Year 2021/2022ObjectiveThis research was carried out to improve student learning outcomes in Class VI SD Negeri 064982 Medan in the 2021/2022 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are 8th grade students of SD Negeri 064982 Medan, the instrument used to obtain data is by using tests, observing the range of values for the test is Value highest and lowest . The instrument used for data processing is to calculate the number of students' scores that have not reached the KKM and the scores that have reached the KKM. The KKM has been set at 70.